Química comparativa entre húmus - Falconieri, Antônio Gautier Farias (1995)
This present work makes a chemical comparison between the natural humus, which was collected in the river-bed of the river Siqueira (Suburbs of Fortaleza - Ce) and the artificial humus obtained from the oxen dung with earthworm. Natural and artificial humus presents an average of humidity of 3,66% and 3,00% respectively. The thermal analysis confirms these data; 3,90% and 3,20% of humidity to the natural and artificial humus. The highest level of humidity on the natural humus is explained by the water being a polar liquid and its dipoles interact eletroctatically with the humus functional groups through the interactions of the Wan Der Walls type. Natural and artificial humus has an average of ashes of 30,12% and 85,08% respectively. The thermal analysis confirms these data; 87,23% and 30,25% of ashes on the natural and artificial humus. This can be understood by the powerful process of natural humus degradation which contributes to the formation of polymer with clayed material; resulting is a different quantity of ashes from natural to artificial humus. The microanalysis of the natural and artificial humus showed the following results to the carbon, hydrogen, nytrogen and oxygen: 0,80% and 20,34% (C), 0,17% and 1,87% (N), 1,25% and 1,87% (H), 97,70% (O) (according to the diference of the sum) when using the anlytical methods, the results were: 0,04% (N) and 0,25% (C) to the artificial humus and 0,02% (N) and 0,23% (C) to the natural humus. According to these results we can notice that the artificial humus has a higher rate of organic material than the natural humus. We observed in the infra-red spectrum that both humus has the same absorption band but they do have different intensity. We observed that 3660cm-1 is attributed to stretching OH and 2928cm-1 is attributed to an axial deformation of C-H. The carboxy group presents absorption in 1864cm-1 which is attributed to an symmetric extending C=O and (according Nakato). This difference corresponds to the coordination of the metal-carboxilatium in the monochelated form. The measures of the conductance in the natural and artificial humus shows a caracteristic curve of strong acid with strong base and weak acid. The equivalence points of the natural and artificial humus were the follwing ones: 0,04M and 0,01M of free acids and 0,02M and 0,14M of combined acids. The analysis indicates a higter brate of Na and Zn to the natural humus than the artificial humus which has a higher rate of K, Fe, Cu, Mn. The Mossbauer spectroscopy through the isomeric shift indicates the oresence of high spin Fe+3 to both humus.